PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN PERTAMBANGAN SUBSEKTOR BATUBARA YANG TERDAFTAR DI BEI - Ni Made Riska Meilan Sari; Gede Putu Agus Jana Susila; Ni Luh Wayan Sayang Telagawathi (Jurnal Akuntansi Profesi, 2020)
The purpose of this study was to examine the effect of liquidity and solvency on profitability both simultaneously and partially. The research design used in this research is causal quantitative. The subjects in this study were coal mining companies listed on the Indonesia Stock Exchange, and the objects in this study were liquidity, solvency, and profitability. Data were collected by recording documents, then analyzed by multiple linear regression analysis. The results showed that (1) liquidity and solvency together have a significant effect on profitability, (2) liquidity and solvency partially have a negative and significant effect on profitability in coal mining companies listed on the Indonesia Stock Exchange.Keywords: liquidity, profitability, solvency